Biophysico-chemical processes of heavy metals and metalloids in soil environments (Wiley-Interscience, 2008)
Written by a multidisciplinary group of soil and environmental scientists, Biophysico-Chemical Processes of Heavy Metals and Metalloids in Soil Environments provides the scientific community with a critical qualitative and quantitative review of the fundamentals of the processes of pollutants in soil environments. The book covers pollutants' speciation, mobility, bioavailability and toxicity, and impacts on development of innovative restoration strategies. In addition, the development of innovative remediation strategies for polluted soils is covered.